Evaluation of a Multi-Session Group Designed to Prevent Commercial Sexual Exploitation of Minors: The "My Life My Choice" Curriculum. Issue 19 (October 2021) - Rothman, Emily F.; Farrell, Amy; Paruk, Jennifer; Bright, Katherine; Bair-Merritt, Megan; Preis, Sarah R.
The commercial sexual exploitation (CSE) of children is a consequential public health and criminal justice problem, but no CSE prevention programs have been evaluated. The Boston-based My Life My Choice (MLMC) program offers a multisession psychoeducation group to girls who are identified as "at-disproportionate-risk" for CSE victimization and trains other agencies throughout the U.S. to offer this curriculum. The curriculum was designed to improve knowledge about the commercial sex industry and shift-related attitudes and behaviors. The current project was a multi-year, multi-site evaluation to assess the effectiveness of the MLMC prevention group. Using a one-group longitudinal design, changes in participant behavior and CSE knowledge were measured at baseline ( n = 354), upon group completion ( n = 296), and 3 months after group completion ( n = 241). The sample was 95% female-identified, 28% Black/African American, 26% White/non-Hispanic, 25% Hispanic/Latina, and 22% other race. The mean age of participants was 15.6 years old. Approximately 28% identified as bisexual, and 10% identified as lesbian, asexual, pansexual, or other. In multivariable-adjusted models, participants reported fewer episodes of sexually explicit behavior at follow up as compared to baseline (relative risk [RR]: 0.52, 95% confidence interval [CI]: 0.37-0.72 at Follow-up 1, and 0.53, 95% CI: 0.35-0.82 at Follow-up 2). Participants were 24% less likely to report dating abuse at Follow-up 2 as compared to baseline ( p = .06). In addition, as compared to baseline, participants were 40% more likely to have given help or information about CSE to a friend at Follow-up 2, and participants demonstrated increased knowledge and awareness about CSE and its harms over the follow-up period. Although additional evaluation using a comparison group and long-term follow up would increase confidence that observed changes are attributable to the group instead of other factors, results suggest that the MLMC curriculum may be effective in reducing the risk of CSE and improving other conditions for youth who are at-disproportionate-risk of CSE.